PEMAKNAAN EKSPLOTASI PEREMPUAN MELALUI IKLAN (STUDI KASUS : PONDS VERSI WHITENING CREAM 2015) - VERA WIJAYANTI SUTJIPTO (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2015)
Abstract This research is about the women exploitation in television advertising. Many companies assume that by using women on advertisement, it could increase the sales. The same perception also applies to Ponds products, which become the object of this research, to find out the meaning of women exploitation through advertising, on the Ponds products consumers, especially on Ponds Whitening Cream 2015 advertising, using the version starred by Raisa, Dea Valencia and Zee Zee Shahab. The researcher uses the encoding decoding model from Stuart Hall. The audience reception will be based on feminism and gender theory to analyze the women exploitation on Ponds advertising. The semiotics theory is also used to analyze the sign and symbol on Ponds advertising. This research is a qualitative research. The drawback of this research is the use of two theories on different research paradigm. The decoding encoding theory is usually used on constructivism paradigm, while the feminism and gender theory is commonly used on critical paradigm. The conclusion of this research is, Ponds advertising is still not relieved from women exploitation, although it has tried to reduced the exploitation perception by choosing models that have achievements. The research suggests that if Ponds want to create a new advertising, choose the models that have different physical attributes than the old advertising, e.g. by choosing the one with curly hair and brown skin. Key words: Advertising, Women Exploitation, Reception Abstrak Penelitian ini, mengenai eksplotasi perempuan dalam iklan televisi. Kebanyakan produsen menggangap bahwa dengan menggunakan perempuan pada iklan, dapat meningkatkan penjualan produk mereka. Pandangan yang sama juga pada produk Ponds, terutama pada iklan Ponds Whitening Cream 2015 versi Selebrities Raisa, Dea Valencia dan Zee Zee Shahab. oleh sebab itu peneliti tertarik untuk mengetahui bagaimana pemaknaan eksplotasi perempuan melalui iklan, dikalangan pengguna produk Ponds tersebut, Teori yang peneliti gunakan, antra lain adalah teori model encoding decoding dari Struat Hall. Khalayak ketika melakukan pemaknaan akan berpedoman pada teori feminisme dan gender sebagai rujukan. Peneliti juga menggunakan teori semiotika ketika menganalisis tanda dan simbol pada iklan Ponds. Penelitian ini adalah penelitian kualitatif, dimana data yang peneliti gunakan adalah hasil dari pengamatan, wawancara dan analisis peneliti. Kelemahan penelitian ini menggunakan dua teori yang dipakai pada paradigma penelitian yang berbeda. Teori decoding encoding biasa digunakan pada paradigma konstruktivisme, sedangkan teori femenisme dan gender biasa dipakai pada paradigma kritis. Kesimpulan penelitian ini adalah iklan ponds pun tidak lepas dari eksploitasi perempuan. Saran dari penelitian ini, sebaiknya Ponds membuat iklan dengan bintang iklan yang mempunyai ciri berbeda dari iklan sebelumnya, seperti bintang iklan yang berambut keriting dan kulit berwarna coklat. Kata Kunci : Iklan, Eksploitasi Perempuan, Pemaknaan